Nursing assistance for elderly patients with HIV/AIDS: integrative review (Research, Society and Development, 2023)
The research aimed to analyze the Brazilian scientific production in the last five years about the nursing care provided to elderly people with HIV (Human Immunodeficiency Virus) / AIDS (Acquired Immunodeficiency Syndrome). This is an integrative review carried out in the following databases: MEDLINE, LILACS and BDENF. The descriptors used were “Aged”, “Acquired Immunodeficiency Syndrome”, “HIV”, “Nursing Care”, “Geriatric Nursing” using the Boolean operators AND and OR. For the inclusion criteria, primary studies in Portuguese from the last five years and available in full were considered. Duplicate studies, theses and dissertations, literature reviews and articles that did not meet the objective of the study were excluded. Of the 119 studies found, 11 were selected. With reading and analysis, it is possible to identify nursing care for elderly people with HIV/AIDS in health education actions, strategies for the dissemination of knowledge among the elderly regarding sexual life, training of professionals and the articulations not only between the different levels of health care, as well as between the multiprofessional teams in the development of preventive, treatment and follow-up actions. It is essential to know and train multidisciplinary teams about the vulnerabilities experienced by the elderly. In addition, there is a need to create public policies, programs and projects, in order to identify early and resolve the consequences of HIV/AIDS infection in the elderly.